Atraksi Pariwisata dalam Mengembangkan Pariwisata Mandeh di Kabupaten Pesisir selatan Sumatera Barat - Rifdatul Husna; Zengga Zengga (JURNAL KAJIAN PARIWISATA DAN BISNIS PERHOTELAN, 2022)
This Paper aims to analyze tourism attractions in developing Mandeh Tourism in Pesisir Selatan District, West Sumatra Province. Data collected from 5 interviewed data sources and 93 respondents using a questionnaire. The research method uses descriptive qualitative methods and SWOT analysis supported by quantitative data in the form of questionnaire data processed using excel. Based on this research, an analysis of tourism attractions in developing tourism is obtained from the elements of attractions: natural beauty, culture and history. By carrying out an analysis (SWOT) to find out what has the potential for tourism attractions in developing the Mandeh Tourism object in Pesisir Selatan Regency.